Dual CCR2/CCR5 antagonist treatment attenuates adipose inflammation, but not microvascular complications in ob/ob mice. Issue 10 (2nd June 2017) - O'Brien, Phillipe D.; Hinder, Lucy M.; Parlee, Sebastian D.; Hayes, John M.; Backus, Carey; Zhang, Hongyu; Ma, Lijun; Sakowski, Stacey A.; Brosius, Frank C.; Feldman, Eva L.
Abstract : Diabetic peripheral neuropathy (DPN) and diabetic kidney disease (DKD) are common diabetic complications with limited treatment options. Experimental studies show that targeting inflammation using chemokine receptor (CCR) antagonists ameliorates DKD, presumably by reducing macrophage accumulation or activation. As inflammation is implicated in DPN development, we assessed whether CCR2 and CCR5 antagonism could also benefit DPN. Five‐week‐old ob/ob mice were fed a diet containing MK‐0812, a dual CCR2‐CCR5 receptor antagonist, for 8 weeks; DPN, DKD and metabolic phenotyping were then performed to determine the effect of CCR inhibition. Although MK‐0812 reduced macrophage accumulation in adipose tissue, the treatment had largely no effect on metabolic parameters, nerve function or kidney disease in ob/ob mice. These results conflict with published data that demonstrate a benefit of CCR antagonists for DKD and hyperglycaemia. We conclude that CCR signaling blockade is ineffective in ob/ob mice and suspect that this is explained by the severe hyperglycaemia found in this model. It remains to be determined whether MK‐0812 treatment, alone or in combination with improved glycaemic control, is useful in preventing diabetic complications in alternate animal models.